Marketing Methods used to Attract the Audience to the Brand (International Journal of Financial, Administrative and Economic Sciences, 2024)
This research tries to examine the marketing tactics utilized to attract the audience to the brand. The study was done on a sample of 150 people, where their data was obtained using well-crafted questionnaires that cover numerous areas of marketing and its influence on customer behavior. After gathering the data, the answers were examined using statistical analysis, using tools such as SPSS, to guarantee the correctness and reliability of the results. The data collected demonstrate that marketing strategies have a vital influence in developing consumers’ attachment with the brand. The statistics suggest that effective marketing methods, such as appealing advertising campaigns, involvement on social media, and delivering relevant material, contribute greatly to boosting customer attachment to businesses. The results also suggest that these strategies encourage consumers’ purchase decisions, as they contribute to giving the required information and aiding comprehension of the advantages of products and services. The study demonstrates that grabbing the audience’s attention is a critical aspect in the marketing plan. The strategies used to grab attention, such as the employment of vivid commercials, social media, and content marketing, have a tremendous influence on growing brand awareness and strengthening its recognition. This study stresses the tremendous relevance of marketing tactics in strengthening brand attachment and motivating purchase decisions, which adds to establishing lasting success for companies in a competitive market.
Keywords: Marketing Methods; Public Relations; Audience; Brand